Learning Model of Islamic Religious Education and Character During the Pandemic Period at SMP Negeri 8 Purwokerto - M Makhful (Ijtimā'iyya, 2021)
The sudden onset of the Covid-19 pandemic has an impact on all aspects of life. In the aspect of education, it is needed how to do it with existing resources, existing technology, education can continue to run well, be conducive and the learning process can be conveyed properly. So that learning can continue, collaboration is maintained, then all elements are responsible for education. Learning Islamic religious education and character will be successful if there is an appropriate model that can be practiced during the pandemic, so that learning continues and can meet expectations.